Sotalol associated polymorphic ventricular tachycardia and coronary spasm. Issue 5 (1st May 1998) - Lowe, M D; Stone, D L; Grace, A A
Abstract : Sotalol may induce torsade de pointes through cardiac action potential prolongation, but a proarrhythmic effect secondary to its β blocking action has not been reported. A 54 year old man presented with symptoms of angina and presyncope, subsequently demonstrated to be associated with coronary spasm. Treatment with sotalol exacerbated his symptoms and resulted in recurrent polymorphic ventricular tachycardia with a pattern indistinguishable from that caused by a class III action. Following sotalol withdrawal polymorphic ventricular tachycardia resolved completely. Polymorphic ventricular tachycardia in patients treated with sotalol may therefore not always be the result of delayed repolarisation, but may be caused by β adrenoceptor blockade.